Modeling of Temperature Dependence of Current in Metal-Oxide-SemiconductorCapacitors after Quasi Breakdown - Fatimah A. Noor; Khairurrijal Khairurrijal (Indonesian Journal of Physics, 2003)
A simple model of temperature dependence of current in MOS capacitors after quasi breakdown was obtained. In developing the simple model, it was assumed that electron traps are created in the oxide layer during high electric field injection of electrons. Further assumptions were that transport of electrons from one trap to another occurs due to an activated process of motion and the traps have an exponential distribution in energy. The results calculated using the model fit well the measured data.